2011
DOI: 10.1074/jbc.m110.186916
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Dihydroceramide Desaturase by Palmitate versus Monounsaturated Fatty Acids

Abstract: Much data implicate saturated fatty acids in deleterious processes associated with obesity, diabetes, and the metabolic syndrome. Many of these changes may be due to aberrant generation of bioactive lipids when saturated fatty acid availability to tissues is increased. On the other hand, studies are emerging that implicate the monounsaturated fatty acid oleate in protection from saturated fat mediated toxicity; however, the mechanisms are not well understood. Our data demonstrate a novel role for palmitate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 59 publications
(18 reference statements)
3
52
0
Order By: Relevance
“…Notably, the monounsaturated fatty acid oleate completely reversed palmitate-induced autophagosome accumulation. Previous studies showed that oleate exerts different cellular effects than palmitate ( 43 ). It prevents lipototoxic effects of palmitate presumably by channelling toxic lipid intermediates of palmitate metabolism to the relatively benign triacylglycerol depot, which we also observed in H9C2 CMs, and may explain its effect on the reversal of palmitateinduced autophagy ( 44 ).…”
Section: Discussionsupporting
confidence: 66%
“…Notably, the monounsaturated fatty acid oleate completely reversed palmitate-induced autophagosome accumulation. Previous studies showed that oleate exerts different cellular effects than palmitate ( 43 ). It prevents lipototoxic effects of palmitate presumably by channelling toxic lipid intermediates of palmitate metabolism to the relatively benign triacylglycerol depot, which we also observed in H9C2 CMs, and may explain its effect on the reversal of palmitateinduced autophagy ( 44 ).…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, wild-type mice fed standard lard-based high-fat diets (LBD) failed to develop a DbCM-like phenotype until very late time points, if at all, and insulin resistance and other aspects of the diabetic phenotype were less pronounced in this model system than in transgenic animals (4)(5)(6)(7)(8)(9). This may result from the high levels of protective unsaturated fatty acids (UFAs) contained in these diets (10)(11)(12). Thus, while these transgenic model systems produce a robust DbCM phenotype, they are unable to reveal clinically relevant roles of specific lipid species in the molecular pathogenesis of DbCM.…”
Section: Introductionmentioning
confidence: 88%
“…Further complicating this effort, previously investigated dietinduced obesity models, which utilize high-fat feeding in wildtype mice, poorly reproduced the cardiac parameters of DbCM, including hypertrophy. This may be because the fatty acid profile of lard, which is the fat source for these diets, contains close to 60% combined oleic and linoleic acids, which have been shown to protect against lipotoxicity and might be expected to attenuate lipotoxic outcomes (11,72).…”
Section: Figurementioning
confidence: 99%
“…Indeed, knockdown of Des1 in cultured myotubes prevented the antagonistic effects of saturated fatty acids on insulin signaling (20,45), and muscles from mice haploinsufficient for Des1 were protected from lipid-and glucocorticoid-induced insulin resistance (16). Moreover, palmitate was shown to induce the enzyme in vitro (20,45), and high-fat feeding did so in vivo (20). Lastly, fenretinide inhibited the enzyme in vivo in both wild-type and high-fat-fed mice, as detected by alterations in ceramide/dihydroceramide ratios, and this accounted at least partially for the drug insulin sensitizing effects (20).…”
Section: Discussionmentioning
confidence: 99%